CREATIVE THINKING AND STUDENTS’ ACHIEVEMENT: A CORRELATIONAL STUDY AT MTS AL FALAH TOROH - Wahyu Unggul Widodo; Nur Iffani Khoirunisa; Etika Dewi Kusumaningyas (LEAD (Language, Education and Development), 2025)
The study aims to analyse the relationship between creative thinking and students' English achievement at MTs Al Falah Toroh. This research employed a quantitative correlational design to investigate the relationship between two variables. The sample consisted of 70 students, selected through a random sampling technique to ensure fairness and representativeness. Data on creative thinking ability were collected using a questionnaire adapted from Dr. Khumar and Dr. Holman, which produced an average score of 67. Meanwhile, students’ English achievement scores were taken from their first-semester report cards, with an average score of 83.83, rounded up to 84. The data were analysed using the Spearman Rank correlation test and processed through SPSS software. The results of the test showed a correlation coefficient of rs (68) = .10 with a significance level of p = .395. This finding indicated a very weak and statistically not significant. In other words, the study found no meaningful relationship between creative thinking and students’ English achievement. The interviews with students and teacher supported these results. They suggest that other factors influence on students’ English achievement, such as the learning environment and educational support facilities, had a greater influence on students’ English achievement.